Enhancing Students’ Listening Skill by Spotify Application - Andi Suwarni; Dewi Sartika; Andi Ika (Hasanuddin University, 2023)
Listening cannot be separated from all activities, but in reality most of the teacher does not pay attention the student's ability to listen and that can affect students' ability in English especially when they want to talk to other people but don’t understand what is being said otherwise because they lack in listening. In the learning process, students may face difficulties one of them is difficulty in conveying speech. Many people say that listening is difficult, due to lack of focus or failure to focus. Therefore, practice concentration by listening more. The objective of the study is to find out spotify podcast application able to enhance the students’ listening skill. The writer apply pre-experimental method with one group pre-test and post-test design, and collected the data based on the test. The research findings showed that the students’ had poor score in pretest. After treatment, their listening ability in identify of listening comprehension increase significantly. The result of the research were the mean score obtained by the students’ through pre-test was 41.6 and post–test was 72.5 with the t-test value orientation is greater than t-table (16.8>2.06). Listening through Spotify podcast in term of identify the listening comprehension 74,2% The result of calculating t-test of the indicators in the students’ t-test listening ability in listening through Spotify podcast application was greater than t-table 24.1>2.06. It can be concluded that spotify podcast application can enhance the students’ ability in listening skill.